Из Именного указателя к «Записным книжкам» Ахматовой [From An Index to Anna Akhmatova’s “Notebooks”] - Timenchik, Roman (Slavica Revalensia, 2019)
This article is yet another installment in the series of Roman Timenchik’s annotations to Anna Akhmatova’s Notebooks (see also the previous volume of Slavica Revalensia). This particular installment concerns the following persons mentioned in Akhmatova’s notes: Natan Al’tman, Lev Bruni, Du Fu (杜甫), Boris Grigor’ev, Aleksei Kepov, Fausto Malcovati, Pyotr Miturich, Alexander Morozov, Vissarion Sayanov (Makhnin), Grigori Sergeyev, Marietta Shaginyan, Nobori Shōmu (昇曙夢), Tinatin Taneyeva (née ჯორჯაძე [Dzhordzhadze]), Boris Tishchenko, and Pyotr Zheleznov. It also includes an entry on the Biblical Holofernes, and the hypostasis of the destructive spirit in Zoroastrianism – Ahriman.